Local Accommodation in the Autonomous Region of Madeira –Property ́s typology and distribution.The Investor Profile - Seixas Sardinha, Luís Filipe (2019)
In the Autonomous Region of Madeira, Local Accommodation has been increasing. It allowed the rehabilitation of degraded properties, offering accommodation in atypical areas and indirectly contributing to other sectors of activity. With an increase in this market, it is important to understand the players.It is within this scope that this empirical study emerged. Through a questionnaire administered to 266 people, it was sought to understand the profile of the investor in this type of market and to map the distribution of the LA in the RAM. In the present study it was possible to demonstrate which municipalities with the most development of realestate affected by LA (Funchal, Calheta and Santa Cruz). It was also possible to verify that in all municipalities there are properties related to this activity, presenting different typologies in more central areas (predominance of apartments) and less centralized areas (predominance of dwellings).The results showed that 62% of the investors are trained at higher level and in a general perspective the respondents have the competencies to act in the market.